Association between Umbilical Catheters and Neonatal Outcomes in Extremely Preterm Infants - Elboraee, Mohamed S.; Toye, Jennifer; Ye, Xiang Y.; Shah, Prakesh S.; Aziz, Khalid; on behalf of the Canadian Neonatal Network Investigators (American Journal of Perinatology, 2018)
Objective The objective of this study was to examine the association between umbilical catheters and a composite outcome of mortality or major neonatal morbidity in extremely preterm infants.Study Design Data were abstracted from the Canadian Neonatal Network database for infants born at <29 weeks' gestational age and admitted to 29 neonatal intensive care units between January 2010 and December 2012. Four groups were identified: those with no umbilical catheters, umbilical venous catheters (UVCs), umbilical artery catheters (UACs), and those with both UVCs and UACs. The outcomes were compared among the groups using univariate and multivariable analyses.Results Of 4,623 eligible infants, 820 (17.7%) had no catheters, 1,032 (22.3%) a UVC only, 120 (2.6%) a UAC only, and 2,651 (57.3%) had both catheters. After adjustment for acuity and other potential confounders, umbilical catheters were associated with higher odds of mortality or any major morbidity (UVC vs. no catheter: adjusted odds ratio [aOR]: 1.47; 95% CI: 1.18–1.85; UAC vs. no catheter: aOR: 1.67; 95% CI: 1.05–2.63; and both UVC + UAC vs. no catheter: aOR: 2.17; 95% CI: 1.79–2.70).Conclusion Most of the infants born at <29 weeks' gestation had UVC and/or UAC placement. The presence of either catheter was associated with mortality or major morbidity, and the association was stronger when both catheters were present.
Keywords: umbilical catheters; extremely preterm infants; neonatal outcomes; mortality or any major morbidity; Canadian Neonatal Network